The Impact of Subjective Norm and Religiosity on Zakat Compliance of Muslim Entrepreneurs: The Mediating Role of Intention - Nurul Ilmi; Ahmad Ajib Ridlwan; A’rasy Fahrullah; Yan Putra Timur; Md. Kausar Alam (Shirkah: Journal of Economics and Business, 2024)
This study aims to identify the effect of Muslim entrepreneurs’ perceptions of zakat compliance mediated by the intention to pay zakat with subjective norms and religiosity. Quantitative methods were employed in this study. Questionnaires were administered to Muslim entrepreneurs, and we examined the information from 140 participants using the Smart-PLS 3 application. The findings indicate that the direct impact on religiosity yielded significant results, whereas the subjective norm was insignificant. Subsequently, the indirect effect, specifically on religiosity and subjective norms, demonstrated a significant impact between the two. In this study, the theory of planned behavior can be used as a determining factor to identify the impact of Muslim entrepreneurs on zakat compliance. This research suggests that Muslim entrepreneurs’ zakat compliance can signal to stakeholders the importance of using zakat payments optimally to achieve poverty reduction goals. Implementing this research not only maximizes institutional benefits in promoting zakat, but also broadens the perspective on zakat compliance among Muslim entrepreneurs based on the theory of planned behavior through intention.